Relationship between Working Tenure and Working Posture with Musculoskeletal Grievance in Batik Madura Workers - Galuh Sistha Prabarukmi1 , Noeroel Widajati2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Batik is one of the cultural heritages of Indonesian people. Batik is the result of acculturationof Javanese, Hindu and Islam which is written on a sheet of fabric. The process of making batik fabrictakes a long time. This condition causes many batik workers experience work related disease, such asmusculoskeletal grievance. This research aimed to analyze the relationship between working tenure andworking posture with musculoskeletal grievance in Batik Madura workers.Methods: This research was an observational research with a cross sectional design. The research populationwas all Batik Madura workers. The sample in this study was 61 Batik Madura workers. The variablesresearched included working tenure, working posture and musculoskeletal grievance.Data were collected by observation, filling out research questionnaires, and Nordic Body Map (NBM). Thedata analysis used was the Spearman correlation.Results: There was no relationship between working tenure with musculoskeletal grievance with a value ofp = 0.837 and there was relationship between working posture with musculoskeletal grievance with a valueof p = 0.000.Conclusion: The working tenure didn’t have relationship with musculoskeletal grievance. The workingposture had a relationship with musculoskeletal grievance.